Augmented Reality's Effect on Online Cosmetics Consumer Purchasing Patterns: A Study on Virtual Artists at Sephora - Dr. RashiBaliyanAshima Jaswal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This work addresses a specific technology that connects the real and the virtual world with the help of Augmented Reality (AR) Technology. This technology allows the users to interact, manipulate and watch 3D virtual media content in a real environment and in real time. For this research qualitative analytical technique have been used with the help of questionnaire and data has been collected with the help of interviews, observation, vlog and blog entries, so this research is an exploratory cum descriptive research highlighting the impact of augmented Reality on buying behavior of consumers in the cosmetic segment. As authors we were not rigid to only particular place for sample collection, we covered the whole Delhi NCR. It is hoped this research will contribute to a better understanding and a broader perspective how augmented reality (AR) creates interest in online shopping and this could be a major step towards developing future strategies for enhancing the online consumer buying experience and augmented reality (AR) advertisements.